ANALISIS LAPORAN REALISASI ANGGARAN DAN SISA LEBIH PERHITUNGAN ANGGARAN (SiLPA) DANA DESA PADA DESA BAILANGU TIMUR KECAMATAN SEKAYU KABUPATEN MUSI BANYUASIN - Supra, Deswati; Asoka, Rano (Jurnal Ilmiah Akuntansi Rahmaniyah, 2024)
This study aims to research about of the 2020-2022 Budget as well as the Analysis of the Budget Realization Report and the 2020-2022 Budget Remaining Balance (SiLPA) and to analyze the treatment of the Remaining Budget Calculation (SiLPA) as well as the Realization of the 2020 to 2022 Budget. This research used a qualitative descriptive method. and was carried out at the Bailangu Timur Village, Sekayu District, Musi Banyuasin Regency. Research data sources in the study used were secondary data. Data collection techniques used in this research were documentation studies, interviews, and literature studies. The results of this study indicated that the Village Fund managed by Bailangu Timur Village, Sekayu District, was a fund sourced from the State Budget (APBN) which was transferred through the APBD (Regional Expenditure Budget), namely In 2020 the budget was Rp. 1,424,279,000, -, in 2021 Budget was Rp. 1,375,607,000, -, and in 2022 the budget was Rp. 1,319,080,000.-. and based on the realization from Bailangu Timur Village in 2020 to 2022 each had a Remaining Budget Calculation (SiLPA) which had been re-budgeted with the same or different activities in that period.